Drug Candidate BGP-15 Prevents Isoproterenol-Induced Arrhythmias and Alters Heart Rate Variability (HRV) in Telemetry-Implanted Rats - Brigitta Bernat; Rita Erdelyi; Laszlo Fazekas; Greta Garami; Reka Maria Szekeres; Barbara Takacs; Mariann Bombicz; Balazs Varga; Fruzsina Sarkany; Arnold Peter Raduly; Dana Diana Romanescu; Zoltan Papp; et al. (Pharmaceuticals, 2023)
Multi-target drug candidate BGP-15 has shown cardioprotective and antiarrhythmic actions in diseased models. Here, we investigated the effects of BGP-15 on ECG and echocardiographic parameters, heart rate variability (HRV), and arrhythmia incidence in telemetry-implanted rats, under beta-adrenergic stimulation by isoproterenol (ISO). In total, 40 rats were implanted with radiotelemetry transmitters. First, dose escalation studies (40–160 mg/kg BGP-15), ECG parameters, and 24 h HRV parameters were assessed. After, rats were divided into Control, Control+BGP-15, ISO, and ISO+BGP-15 subgroups for 2 weeks. ECG recordings were obtained from conscious rats, arrhythmias and HRV parameters were assessed, and echocardiography was carried out. ISO-BGP-15 interaction was also evaluated on an isolated canine cardiomyocyte model. BGP-15 had no observable effects on the ECG waveforms; however, it decreased heart rate. HRV monitoring showed that BGP-15 increased RMSSD, SD1, and HF% parameters. BGP-15 failed to counteract 1 mg/kg ISO-induced tachycardia, but diminished the ECG of ischemia and suppressed ventricular arrhythmia incidence. Under echocardiography, after low-dose ISO injection, BGP-15 administration lowered HR and atrial velocities, and increased end-diastolic volume and ventricle relaxation, but did not counteract the positive inotropic effects of ISO. Two weeks of BGP-15 treatment also improved diastolic function in ISO-treated rats. In isolated cardiomyocytes, BGP-15 prevented 100 nM ISO-induced aftercontractions. Here, we show that BGP-15 increases vagally mediated HRV, reduces arrhythmogenesis, enhances left ventricle relaxation, and suppresses the aftercontractions of cardiomyocytes. As the drug is well tolerated, it may have a clinical value in preventing fatal arrhythmias.